2019
DOI: 10.5014/ajot.2019.027599
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Challenges in Military Service Members With Chronic Mild Traumatic Brain Injury

Abstract: OBJECTIVE. The purpose of this study was to identify the needs of military service members with chronic symptoms after mild traumatic brain injury (mTBI) that fall within the scope of occupational therapy practice. METHOD. In this qualitative descriptive study, service members with a history of mTBI (N = 12) participated in semistructured interviews about their injury history, symptoms, daily routines, challenges, and plans. RESULTS. Two main themes were identified: occupational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Family participation in occupational therapy was highly valued by both service members and clinicians in the present study, which implies that it is important to include family in therapy consistently. Furthermore, participants in our earlier needs assessment study identified family members as their strongest sources of support (Cogan et al, 2019). Foster et al (2012) recommended that family incorporation in care be structured and purposeful, including early engagement, cultural adaptation, education and training, and support for community reintegration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Family participation in occupational therapy was highly valued by both service members and clinicians in the present study, which implies that it is important to include family in therapy consistently. Furthermore, participants in our earlier needs assessment study identified family members as their strongest sources of support (Cogan et al, 2019). Foster et al (2012) recommended that family incorporation in care be structured and purposeful, including early engagement, cultural adaptation, education and training, and support for community reintegration.…”
Section: Discussionmentioning
confidence: 99%
“…Most service member participants reported a lack of interest in previously enjoyable activities, difficulty in performing work duties, and cognitive issues that interfered with instrumental activities of daily living. Service members in that study reported having strong family support concurrent with fears of unemployment or worsening health problems in the future (Cogan et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The second author (Haines) was an active-duty service member at the time of the study, which informed her interpretations of the data. Results of the main research questions for the study related to occupational therapy treatment are published elsewhere (Cogan, Haines, Devore, Lepore and Ryan 2019; Cogan, Philip, and Huang 2018). All names used are pseudonyms.…”
Section: Methodsmentioning
confidence: 99%